Experimental and kinetic analysis of the addition of zerovalent iron for promoting conversion of CO2 into CH4 by anaerobic sludge - Maneerat Khemkhao; Sengthong Lee; Chantaraporn Phalakornkule; Vichai Domrongpokkaphan (Journal of Applied Science and Engineering)
Reducing greenhouse gas (GHG) emissions and sequestering carbon dioxide (CO2) can be achieved by a reduction of CO2 to methane (CH4) for renewable energy production. This study used zero-valent iron (ZVI) as an electron donor to reduce CO2 to CH4 at different ZVI concentrations (16, 32, 64, 96, and 224 g/L). The experimental CO2 consumption rates for the reactor with 16, 32, 64, 96, and 224 g/L ZVI were 6.880, 5.438, 7.384, 8.309, and 8.051mmol/d · Lreactor, respectively. The CO2 reduction kinetics was analyzed using four models (Cone, Gompertz, Logistic, and Richards equations). The four models, especially the Richards equation, satisfactorily fitted the experimental data with an R^2 of 0.990 − 0.998. The derived kinetic parameters reflected the experimental results, which showed that the lag phase for methane production decreased with increasing ZVI concentrations. The other characteristics of the system were: (1) the ZVI addition caused the increase in pH of the media; (2) there was a competition between methanogens and other metabolic pathways, especially at relatively high pH; and (3) relatively high ZVI concentrations induced the production of acetate and propionate.